Social, environmental and psychological factors associated with objective physical activity levels in the over 65s. - Marion E T McMurdo; Ishbel Argo; Iain K Crombie; Zhiqiang Feng; Falko F Sniehotta; Thenmalar Vadiveloo; Miles D Witham; Peter T Donnan (PLoS ONE)
Objective To assess physical activity levels objectively using accelerometers in community dwelling over 65 s and to examine associations with health, social, environmental and psychological factors. Design Cross sectional survey. Setting 17 general practices in Scotland, United Kingdom. Participants Random sampling of over 65 s registered with the practices in four strata young-old (65-80 years), old-old (over 80 years), more affluent and less affluent groups. Main outcome measures Accelerometry counts of activity per day. Associations between activity and Theory of Planned Behaviour variables, the physical environment, health, wellbeing and demographic variables were examined with multiple regression analysis and multilevel modelling. Results 547 older people (mean (SD) age 79(8) years, 54% female) were analysed representing 94% of those surveyed. Accelerometry counts were highest in the affluent younger group, followed by the deprived younger group, with lowest levels in the deprived over 80 s group. Multiple regression analysis showed that lower age, higher perceived behavioural control, the physical function subscale of SF-36, and having someone nearby to turn to were all independently associated with higher physical activity levels (R(2) = 0.32). In addition, hours of sunshine were independently significantly associated with greater physical activity in a multilevel model. Conclusions Other than age and hours of sunlight, the variables identified are modifiable, and provide a strong basis for the future development of novel multidimensional interventions aimed at increasing activity participation in later life.